Advanced concepts for intelligent vision systems : 17th International Conference, ACIVS 2016, Lecce, Italy, October 24-27, 2016, Proceedings /: 17th International Conference, ACIVS 2016, Lecce, Italy, October 24-27, 2016, Proceedings. (2016) - Unknown
No abstract available